The Analysis of Crowdfunding Implementation as an Alternative Financing for Islamic Microfinance Institution - Karimah, Diva Azka; Tamanni, Luqyan; Indra, Indra; Pamuncak, Mohammad Bintang (AL-MUZARA'AH, 2025)
Islamic Microfinance Institutions (IMFIs) play a crucial role in delivering financial services to Micro, Small, and Medium Enterprises (MSMEs), thereby advancing financial inclusion and fostering economic empowerment. Despite their significance, IMFIs frequently encounter major constraints, particularly limited access to capital. In contrast, technological advancements have introduced innovative and efficient financing alternatives, most notably in the form of financial technology (fintech). This study investigates the potential for collaboration between IMFIs and fintech, with a particular emphasis on crowdfunding as a financing mechanism. It seeks to identify the benefits and opportunities, alongside the costs and risks, associated with the implementation of fintech-based crowdfunding as an alternative financing source for IMFIs. Adopting a critical review research paradigm and a mixed-method epistemological approach, the study employs two key methodologies: (1) the development of a typology outlining the benefits, opportunities, costs, and risks of collaboration; and (2) the application of the Analytic Network Process (ANP), using the typology as the foundation for model construction. Findings indicate that experts generally perceive the benefits and opportunities of such collaboration to outweigh the associated costs and risks. Notable advantages include enhanced access to capital and the cultivation of a more robust investment culture within IMFIs. On the other hand, key concerns include infrastructural limitations and the potential for capital loss. To mitigate these risks and maximize collaborative benefits, the study highlights the importance of strengthening institutional management across both IMFIs and fintech platforms.